(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The paper presents important standards that need to be considered by educational organizations when auditing their quality management systems. Traditionally, these quality management systems are based on ISO 9001, and are audited based on ISO 19011. Starting in 2018, a new standard - ISO 21001 provides requirements and guidance for the management systems of educational organizations, including universities. In 2025 all of the three standards mentioned above are undergoing changes that will affect the way educational quality management systems are developed, implemented, audited, and improved.